(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This review study addresses the chemical safety of milk and dairy products, focusing on the dynamics of lead (Pb) and cadmium (Cd) accumulation. The research explores the complex pathways of these heavy metals, starting from environmental sources like contaminated soil, water, and phosphate fertilizers, through bioaccumulation in livestock, and ending with their secretion into milk. A critical focus is placed on the "manufacturing intensification" effect, where technological processes such as evaporation and curdling significantly concentrate these toxins in products like cheese. The study also evaluates the severe health risks, particularly neurotoxicity and nephrotoxicity, posed to sensitive groups like children. By synthesizing global data and international standards (Codex, EU), the paper provides strategic recommendations for monitoring environmental inputs and implementing advanced filtration technologies to ensure dairy safety.